Does Dedicated Research Time During Residency Predict Resident Academic Productivity and a Future Academic Career?. (May 2022) - Onyekaba, Ginikanwa; Mauch, Jaclyn T.; Barrero, Carlos; Mellia, Joseph A.; Diatta, Fortunay; Card, Elizabeth; Broach, Robyn B.; Fischer, John P.
Abstract : Objective: Dedicated research time is a component of certain plastic surgery programs, and yet, there is limited research examining its impact on academic productivity and career outcomes. This study aimed to assess the effect of dedicated research time on the academic productivity of residents and the likelihood of pursuing an academic career. Methods: We conducted a cross-sectional study that examined bibliometric indices of integrated plastic surgery residency graduates from 2010 to 2020. Academic productivity was determined by the number of peer-reviewed publications and h-index 1 year after residency graduation. Results were analyzed using descriptive statistics, χ 2 test, t test, and logistic regression. Results: Data on plastic surgery residency graduates were analyzed (N = 490 from 46 programs). The mean numbers of publications and h-index per research track graduate were 26.1 and 8.23, respectively. The mean numbers of publications and h-index per nonresearch track graduate were 15.9 and 5.97, respectively. After controlling for the University of Alabama research ranking through multilinear regression analysis, we found that pursuing dedicated research time was an independent predictor of increased h-index and publication output, although it did not predict an increased likelihood of pursuing an academic career. Conclusions: Participating in dedicated research during residency increases academic productivity, irrespective of the residency program's research rank. Given this finding, offering research years can help support the mission of fostering academic opportunities within plastic surgery.